2015
DOI: 10.1002/hed.24011
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral lymphatic vessel density as a predictor of progression‐free and overall survival in locally advanced laryngeal/hypopharyngeal cancer

Abstract: Intratumoral lymphatic vessel density is predictive of PFS and OS in locally advanced laryngeal/hypopharyngeal cancer. © 2015 Wiley Periodicals, Inc. Head Neck 38: E417-E420, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…While much attention is given to hematological transit of cancer cells, and most chemotherapy is delivered intravenously, metastatic spread is most often initiated through tumor-draining lymphatics to regional draining LNs before draining into and disseminating through the blood circulation. Expanded peritumoral lymphangiogenesis is frequently observed as part of cancer progression and correlates with increased LN metastasis and poorer survival [51,52], further evidencing that the lymphatics provide a highway for system dissemination. However, before cancer cells metastasize through these peritumoral lymphatics, tumor antigens (tAgs) and mature, activated dendritic cells presenting tAgs migrate through the peritumoral lymphatics to regional LNs to set up anti-tumor immune responses (Figure 1).…”
Section: The Effects Of Metastasis and Cancer Progression On Lymphatimentioning
confidence: 99%
“…While much attention is given to hematological transit of cancer cells, and most chemotherapy is delivered intravenously, metastatic spread is most often initiated through tumor-draining lymphatics to regional draining LNs before draining into and disseminating through the blood circulation. Expanded peritumoral lymphangiogenesis is frequently observed as part of cancer progression and correlates with increased LN metastasis and poorer survival [51,52], further evidencing that the lymphatics provide a highway for system dissemination. However, before cancer cells metastasize through these peritumoral lymphatics, tumor antigens (tAgs) and mature, activated dendritic cells presenting tAgs migrate through the peritumoral lymphatics to regional LNs to set up anti-tumor immune responses (Figure 1).…”
Section: The Effects Of Metastasis and Cancer Progression On Lymphatimentioning
confidence: 99%
“…LN metastasis is considered a crucial prognostic factor for various cancers. 30 31 32 In a previous study, we found that high expression of VEGF-C is related to increased lymphatic vessel density (LVD) and lymphatic vessel invasion (LVI) in PCa, which could promote LN metastasis and lead to poor prognosis. 23 The significance of VEGF-C in lymphangiogenesis and LN metastasis in human malignancies has been widely recognized, 33 34 35 while TLR9 may upregulate VEGF-C by activating nuclear factor kappa B (NF-κB).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that high MVD is associated with both metastasis and poor prognosis in patients with head and neck cancers . Lymphatic vasculature has also been shown to play a role, with high LVD being associated with poor prognosis in gastric, non‐small‐cell lung, and head and neck cancers . Many of these studies have distinguished between peritumoral and intratumoral vessel densities.…”
Section: Discussionmentioning
confidence: 99%
“…9,22 Lymphatic vasculature has also been shown to play a role, with high LVD being associated with poor prognosis in gastric, non-small-cell lung, and head and neck cancers. 10,11,[23][24][25][26][27][28] Many of these studies have distinguished between peritumoral and intratumoral vessel densities. In HNSCC, high intratumoral LVD has been reported to be associated with higher risk of local recurrence, 10 cervical nodal metastases, 11,29 and worse overall survival.…”
Section: Discussionmentioning
confidence: 99%